The Influence of E-Service Quality and Brand Image on Customer E-Loyalty Through Customer E-Satisfaction Among PLN Mobile Users in PT. PLN UIW Bangka Belitung - Rahmat Abdul Kharisma; Heppy Millanyani (Ann Publisher, 2026)
Background. This study examines the determinants of digital customer loyalty in public utility services through The Influence of E-Service Quality and Brand Image on Customer E-Loyalty Through Customer E-Satisfaction Among PLN Mobile Users in PT. PLN UIW Bangka Belitung. Despite high installation rates of PLN Mobile, active user engagement remains relatively low, indicating a gap between adoption and sustained usage behavior. Methods. A quantitative explanatory research design was employed using purposive sampling of 437 PLN Mobile users in PT. PLN UIW Bangka Belitung. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares to evaluate measurement and structural relationships. Results. The findings indicate that e-service quality and brand image significantly and positively influence customer e-satisfaction. Customer e-satisfaction demonstrates the strongest direct effect on customer e-loyalty. The total effect analysis confirms that e-service quality and brand image exert significant overall influence on customer e-loyalty through both direct and mediated pathways. The structural model shows substantial explanatory power in predicting digital loyalty behavior within a public utility context. Conclusions. This study confirms that e-service quality and brand image exert significant total effects on customer e-loyalty through the mediating role of customer e-satisfaction. Customer e-satisfaction serves as the primary explanatory mechanism that converts digital service performance and brand perception into sustained loyalty behavior within a public utility context. The findings imply that strengthening application reliability, personalization features, and brand credibility is essential to enhance long-term digital engagement and retention in public sector service platforms.